Panca Siksaning Angaji for Strengthening Character Education in the Concept of Ethnopedagogy Based on Balinese Local Wisdom - Gunada, I Wayan Agus; Harnika, Ni Nyoman; Lestari, Ni Wayan Ria (Jurnal Penelitian Agama Hindu, 2025)
Adapting and internalizing concepts in local wisdom is very important to strengthen the character of students, in the midst of the onslaught of juvenile delinquency. One of the concepts of Balinese local wisdom in the aspect of education is the concept of Panca Siksaning Angaji. This concept is not only a learning model, but contains social, cultural, and spiritual values and is ideal to be internalized in character building. Based on this, this study aims to analyze the importance of the concept of the panca siksaning angaji in strengthening character education for students. The analysis was carried out with a qualitative research approach to literature review, based on relevant Balinese literature. Based on the results of the research, the panca siksaning angaji consist of the aspects of gugu, teleb, inget, wiweka and laksana. Gugu is interpreted as the process of initiating confidence in students, Teleb instills the principle of seriousness, Inget means strengthening the understanding of character values, Wiweka applies critical and creative thinking, and Laksana means the application of character values in students' daily lives. The five interrelated parts strengthen character education based on local Balinese wisdom, and ideally can be internalized in students who are integrated into the daily learning process. This research can help increase insight into the importance of character education based on local wisdom, especially Balinese culture, to form a superior and characterful young generation in Indonesia.